Asma Barlas’ Criticism of Hadith as a Tool of Tafsir: Critical Analysis of Feminist’s Predominant Narrative - Ilyasu Adam, Dr. Ibrahim (Journal of Quranic and Social Studies, 2023)
This paper evaluates the hermeneutical methodology of Asma Barlas, in critiquing Muslims’ intellectual traditions with a special reference to the Prophetic tradition, the Sunnah, and its relevance in understanding Islam. In Islamic orthodoxy, the Sunnah occupies the second position as a source of Islamic law. More importantly, it serves as practical explanation of the Qur’ān. Consequently, the Sunnah has become indispensable in understanding the Qur’ān. Conversely, Barlas uses her hermeneutical methodology to challenge the authenticity of the Sunnah and its role in understanding the Qur’ān.1 Her central argument is that using the Sunnah to interpret the Qur’ān is problematic as it undercuts the doctrine of revelation’s self-sufficiency and the interpretive flexibility inherent in it, putting a methodological closure on how the Qur’ān could ‘‘legitimately’’ be read 2 Her criticism of hadith as a tool of tafsīr is specifically remarkable. This paper, therefore, critically analyzes Barlas’ hermeneutical methodology in relation to her criticism of hadith as an important ingredient of tafsīr. It argues that hadith is an indispensable tool in making sound Qur’anic interpretation and in proper understanding of the Qur’ān as a source of guidance to humanity. It then analyses Barlas’ arguments making references to her intellectual inadequacy. The paper concludes that Barlas’ argument on the position of the Sunnah in Islam is simplistic; while not denying that a significant amount of hadith were forged and integrated into tafsīr, it must be stressed that this forgery was not allowed to go unchallenged